An economic analysis of eradicating alien vegetation as an alternative to conventional water supply schemes: a case study of the Krom and Kouga - Carpenter, Robert Charles (Rhodes University, Faculty of Commerce, Department of Economics, 1999)
South Africa is classified as an arid to semi-arid region and water scarcity in South Africa has been identified as a key factor limiting socioeconomic development in the next century. In the Algoa region, the total urban plus agricultural water demand is expected to exceed the supply by the year 2005. The Kouga Working for Water Project aims to increase the base flow to the existing dams which supply the Port Elizabeth metropolitan area through the eradication of invasive alien trees in the riparian areas of the Krom and Kouga catchments. This thesis analyses the economic efficiency of optimal catchment management as a water supply scheme. A cost-benefit analysis is conducted for the Kouga eradication programme, and its desirability is evaluated in terms of the net present value (NPV) and the internal rate of return (IRR) criteria. In order to compare the cost-e~i.ciency of the eradication programme to alternative water supply augmentation schemes the Unit Reference Value (URV) is calculated for the project. The NPV for the project is calculated using a discount rate of 7% and amounts to nearly R24 million. This positive NPV indicates that the project is economically desirable in that it results in the improvement of human welfare. The IRR decision rule supports this finding. The URV of the eradication scheme is found to be competitive to that generated by more conventional schemes. Considered in the evaluation of the project are a host of environmental benefits that accompany the eradication of alien vegetation. This is in contrast to alternative schemes which result in several detrimental impacts to the environment. The economic analysis concludes that the eradication of alien vegetation is an efficient and desirable alternative water supply augmentation scheme. The conclusions drawn from the analysis of the eradication programme in this catchment area can be extended to other catchment areas, with the aim of promoting the most efficient supply of water.
Keywords: Alien plants -- South Africa; Water-supply -- South Africa; Kouga River (South Africa)